2019
DOI: 10.1523/eneuro.0220-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Diverse Classes of Cholecystokinin Interneurons in the Basal Amygdala Facilitates Fear Extinction

Abstract: There is growing evidence that interneurons (INs) orchestrate neural activity and plasticity in corticoamygdala circuits to regulate fear behaviors. However, defining the precise role of cholecystokinin-expressing INs (CCK INs) remains elusive due to the technical challenge of parsing this population from CCK-expressing principal neurons (CCK PNs). Here, we used an intersectional genetic strategy in CCK-Cre;Dlx5/6-Flpe double-transgenic mice to study the anatomical, molecular and electrophysiological propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 65 publications
(99 reference statements)
10
25
0
Order By: Relevance
“…We found that 7-9 % of all inhibitory cells in the LA and BA are CCK+/CB1+ basket cells, a ratio, which is similar to that estimated in the hippocampus (Bezaire and Soltesz, 2013). Of note, in this novel transgenic mouse line we have not sampled fast spiking cells or neurogliaform cells, interneuron types that could be often targeted in Cck Cre ;Dlx5/6 Flp mice, in addition to CCK+/CB1+ basket cells (Rovira-Esteban et al, 2019). These data suggest that the two strategies, the knock-in vs. the use of BAC as a tool to generate transgenic lines, produce mice that express the Cre recombinase or fluorescent proteins in distinct populations of CCK+ inhibitory cells, yet CB1+ basket cells are always affected, albeit with a different efficacy.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that 7-9 % of all inhibitory cells in the LA and BA are CCK+/CB1+ basket cells, a ratio, which is similar to that estimated in the hippocampus (Bezaire and Soltesz, 2013). Of note, in this novel transgenic mouse line we have not sampled fast spiking cells or neurogliaform cells, interneuron types that could be often targeted in Cck Cre ;Dlx5/6 Flp mice, in addition to CCK+/CB1+ basket cells (Rovira-Esteban et al, 2019). These data suggest that the two strategies, the knock-in vs. the use of BAC as a tool to generate transgenic lines, produce mice that express the Cre recombinase or fluorescent proteins in distinct populations of CCK+ inhibitory cells, yet CB1+ basket cells are always affected, albeit with a different efficacy.…”
Section: Discussionsupporting
confidence: 74%
“…We took advantage of the fact that in adult Pvalb-Cre, Sst-Cre and Vip-Cre mice viral labeling visualizes one or two GABAergic cell categories that can be separated by immunostaining. In Pvalb-Cre mice, fast spiking basket cells and axo-axonic cells could be distinguished based on the CB content (Bienvenu et al, 2012; Vereczki et al, 2016; Andrasi et al, 2017; Rovira-Esteban et al, 2019). We estimated that 17 % and 20 % of all GABAergic cells are PV+ basket cells in the LA and BA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this interpretation of the data, optogenetic inhibition of PV positive cells in BLA was sufficient to rescue the low freezing phenotype of PND 21 LB reared mice. However, other inhibitory neuronal populations within the BLA are also capable of modulating fear expression (Krabbe et al, 2018;Lucas and Clem, 2018;Rovira-Esteban et al, 2019;Wolff et al, 2014), thus, questions regarding the potential of other populations of neurons to be able to mask the effect of LB rearing remain to be explored. Although we did not observe differences between LB and control mice in somatostatin or VGLUT 2 cell densities at PND 21, this does not rule out the possibility of changes in physiological properties of these classes of cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific circuit and behavioral roles of CB 1 /CCK-positive interneurons have remained rather elusive. The incomplete and inaccurate cell-type-specific expression of genetic regulatory tools in CB 1 /CCK-positive interneurons renders in vivo experimental manipulation of their physiological and behavioral functions difficult ( Rovira-Esteban et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%